The Influence of Brand Equity of Wings Products on the Business Development of PT. Surya Setia Sejahtera during the Covid-19 Pandemic, Palu, Central Sulawesi - Sarifuddin T; Mega Purnama (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
This study aims to determine the effect of the Brand Equity of Wings products on the business development of PT. Surya Setia Sejahtera Palu, using an explanatory research approach, while the total sample is 50 consumers of Wings products, with data collection techniques using a questionnaire. The calculation results, using multiple linear regression model analysis, based on the results of the F test, show that the Brand Equity Wings product, which consists of variables Brand awareness, Perceived quality, Brand association, and Brand loyalty jointly (simultaneously) have a significant effect on the business development variable of PT. Surya Setia Prosperous Palu. The t-test calculations show that the Brand awareness variable partially does not substantially impact the business development variable of PT. Surya Setia Prosperous Palu. While the variables Perceived quality (X2), Brand association, and Brand loyalty partially have a significant influence on the Wings Product business development variable at PT. Surya Setia Prosperous Palu.